DA'WAH COMMUNICATION BIL LISAN IN THE FDKI MENGAJI PROGRAM OF IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG - Azfa, Pani; Amrullah; Iqrom Faldiansyah; Gustin (MEDIOVA: Journal of Islamic Media Studies, 2025)
The implementation of da'wah (Islamic preaching) in the campus environment aims to develop spiritual values based on content and media. Activities are carried out in the form of religious, social, and community-based events. Da'wah institutions can grow effectively when strengthened by a sense of responsibility and loyalty from the institution’s management. However, challenges commonly faced by da'wah institutions include limited social outreach, lack of funding, and a small number of active members involved in the management. This research aims to describe verbal da'wah communication (da'wah bil lisan) in the "FDKI Mengaji" program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. This study uses a qualitative method with primary data sources from the managers of the FDKI Mengaji program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. Data were collected through interviews, observation, and documentation, and analyzed using qualitative data analysis techniques. Verbal da'wah communication in the FDKI Mengaji Program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung is conducted through direct sermons delivered by two preachers simultaneously, which has successfully attracted public enthusiasm to attend the da'wah events. The FDKI Mengaji program also benefits from strong mutual support among its managers, fostered through a sense of togetherness and a solid commitment. This verbal da'wah also serves as a form of community service in each program. The form of da'wah bil lisan used is adapted to the needs of the community and represents the sole officially mandated da'wah program by IAIN Syaikh Abdurrahman Siddik Bangka Belitung.